Table of Content - - (Arab Journal for Sciences and Research Publishing, 2023)
Table of Content:1. The purposes of The Holy Qura’n in the instruments of gaining wealthLecturer. Mohammed Abdulrab Sharaf Lutf, Prof. Zakaria Hama2. The reasons for intellectual differences from the perspective of Islamic law, and the role of Saudi universities in confronting themDr. Sekina Mohamed Mohamed Abd El Halim, Dr. Amal Abd El Aziz Mohamed Ghazy3. Semiotics of the Saudi heritage in the light of contemporary technologyLecturer \ Manal Eid Sanusi Abjabal, Co-Prof. Foton Fouad Fayoumi4. The effects of the Corona pandemic on the current and future situation of organizing and holding events and occasions: a field study on the General Entertainment Authority in Kingdom of Saudi ArabiaMr. Rayan Abdul-Aziz Iraqi, Mr. Shaheen Sulaiman Al-Abdali, Dr. Mansour Talal Abid Alansari5. Spatial analysis of residential land prices in Jeddah cityMr. Alsharif Shaker Abdullah6. Palestinian Scientific Research from the Perspective of Master's Students: Exploring Reality and AspirationsDr. Osama Matar1, Dr. Reem Jawabreh, Mrs. Haya Radwan, Mr. Abedelrahman Alhajhamad, Dr. Mohammad Ayyash, Mrs. Sherin Kaleef, Mr. Thaher Gharabeh, Dr. Ashraf Abualrob, Mrs. Aseel Halabi, Mr. Diya Abu Shomer7. Piecewise Linear Discontinuous Petrov Galerkin Method for Time Fractional Diffusion EquationsDr. Basheer Saleh Abdallah
Keywords: Arab Journal of Sciences & Research Publishing